Prevalence and demographic distribution of Helicobacter pylori infection among dyspeptic patients attending a tertiary care hospital in Bangladesh - Paul, Swarna; Chowdhury, Shaheen Akhter; Jannat, Masuma; Paul, Showmik; Rima, Shamim Ara; Prima, Boosra Harun; Das, Saurav; Mitra, Puja; Tania, Zannatul Ferdous; Khan, Ayesha Ahmed (International Journal of Research in Medical Sciences, 2025)
Background: Helicobacter pylori are a Gram-negative, spiral-shaped bacterium that colonizes the human stomach and is one of the most common chronic infections worldwide. It plays a critical role in the pathogenesis of various gastrointestinal disorders. Therefore, this study aims to determine the prevalence of H. pylori infection among dyspeptic patients attending a tertiary care hospital in Bangladesh and to analyze its demographic distribution. Methods: This cross-sectional descriptive study was conducted in the Department of Microbiology, Chittagong Medical College, Chattogram, from January 2021 to December 2021. Suspected PUD patients with dyspepsia attending outdoors and admitted to the Department of Gastroenterology, CMCH were included. Among them, upper GI endoscopy was done in 130 symptomatic patients. SPSS (Statistical Package for Social Sciences) for Windows version 20 software was used for analysis. Results: In this study of 130 dyspeptic patients, the majority (55.4%) were aged 20–40 years, with a male predominance (male-to-female ratio 1.45:1) and a mean age of 39.56±14.38 years. Helicobacter pylori were detected in 67.7% of patients by culture and in 74.6% by PCR, indicating the higher sensitivity of molecular diagnostics. Endoscopic evaluation revealed normal findings in 40% of cases, while antral gastritis (31.5%) was the most common abnormality, followed by duodenal ulcer (9.2%), gastric ulcer (8.4%), antral erosion (8.4%) and reflux oesophagitis (2.3%). Conclusions: The present study highlights the significant prevalence of Helicobacter pylori infection among dyspeptic patients, particularly in individuals below the age of 40. The findings underscore the importance of age and gender as key demographic factors associated with H. pylori infection, with a noticeable male predominance and a higher prevalence in younger age groups.